2020
DOI: 10.1617/s11527-020-01583-9
|View full text |Cite
|
Sign up to set email alerts
|

Analytical model for masonry walls strengthened with vegetal fabric reinforced cementitious matrix (FRCM) composites and subjected to cyclic loads

Abstract: Masonry is one of the eldest construction systems in the building industry, currently in use because some advantages like compressive capacity, traditional aesthetics, low cost and good practices. However, damages recorded in walls as a result of cyclic loads, have given rise to an important development in the area of strengthening and rehabilitation of this type of structural element. To counteract this problem, the vegetal FRCM arises as a strengthening competitive system for the improvement of the mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…This study represents the continuation of experimental and analytical studies previously presented by the authors [18] [19]. Therefore, the main objective of this study is to develop numerical models capable to reproduce the experimental and analytical behavior of walls strengthened with FRCM of vegetal fibres.…”
Section: Introductionmentioning
confidence: 79%
“…This study represents the continuation of experimental and analytical studies previously presented by the authors [18] [19]. Therefore, the main objective of this study is to develop numerical models capable to reproduce the experimental and analytical behavior of walls strengthened with FRCM of vegetal fibres.…”
Section: Introductionmentioning
confidence: 79%
“…To define the mechanical properties of each FRCM (shell elements), it was necessary to implement FRCM models (fabric and mortar) and to determine its tensile behavior with the procedure presented in [ 40 ].…”
Section: Numerical Modelsmentioning
confidence: 99%
“…For the interaction between the shell elements (FRCMs) and deformable solids (the concrete beam), a tie connection was used. This approach was considered in other studies [ 40 , 41 ]. A tie connection is a link restriction that allows merging two regions, even though the meshes created on the surfaces of the regions may be different, so complete beam–FRCM bonding can be assumed.…”
Section: Numerical Modelsmentioning
confidence: 99%
“…A composite system consisting of continuous multiaxial hybrid fibers embedded in the mortar-based matrix was proposed and denominated Textile Reinforced Mortar (TRM). Internationally, the inorganic composite systems reinforced by textile are also named Textile Reinforced Concrete/Cement (TRC) (Bisby et al, 2011;Cheng et al, 2020), Fiber Reinforced Cementitious Matrix/Mortar (FRCM) (Del Zoppo et al, 2019a;Mercedes et al, 2020), Cementitious Matrix Grid (CMG) (Prota et al, 2006), Composite Reinforced Mortar (CRM) (Del Zoppo et al, 2019b), or Inorganic Matrix-Grid (IMG) (Augenti et al, 2011;Parisi et al, 2013). The research has shown that the application of TRM is served as an alternative to the application of FRP.…”
Section: Introductionmentioning
confidence: 99%